2008
DOI: 10.1093/jxb/ern138
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-induced differential gene expression during abscission of citrus leaves

Abstract: The main objective of this work was to identify and classify genes involved in the process of leaf abscission in Clementina de Nules (Citrus clementina Hort. Ex Tan.). A 7 K unigene citrus cDNA microarray containing 12 K spots was used to characterize the transcriptome of the ethylene-induced abscission process in laminar abscission zone-enriched tissues and the petiole of debladed leaf explants. In these conditions, ethylene induced 100% leaf explant abscission in 72 h while, in air-treated samples, the absci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
2
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(147 citation statements)
references
References 86 publications
12
118
2
15
Order By: Relevance
“…These results indicate that a similar mechanism regulates abscission for both detached fruits in agar medium and attached fruits on the tree. Detached leaf explant incubation has also been performed to investigate the leaf abscission process in citrus (Agustí et al, 2008). We conclude that incubation of detached fruits in agar medium is a useful method for inducing fruit abscission.…”
Section: Discussionmentioning
confidence: 92%
“…These results indicate that a similar mechanism regulates abscission for both detached fruits in agar medium and attached fruits on the tree. Detached leaf explant incubation has also been performed to investigate the leaf abscission process in citrus (Agustí et al, 2008). We conclude that incubation of detached fruits in agar medium is a useful method for inducing fruit abscission.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement, Gómez-Cadenas et al (1996; pointed out the key role of ethylene as activator of leaf abscission in waterstressed citrus trees, and suggested that ABA was the primary stress signal responsible for the increase in ethylene. Work performed in citrus fruit further revealed a crosstalk between ABA and ethylene for triggering fruit abscission (Gómez-Cadenas et al, 2000;Agustí et al, 2008). Results obtained in mature sweet cherry, which are very prone to abscission, suggested, however, that the ABA increase observed at late stages of fruit ripening was more likely related to Introduction ethylene in the development and ripening of climacteric fruits, such as nectarine and tomato, is well known (Ziliotto et al, 2008;Zhang et al, 2009b) since several reports suggested that the ABA accumulation just before the peak of ethylene production triggers ethylene biosynthesis responsible for climacteric fruit ripening (Zhang et al, 2001;Zhang et al, 2009a;Bastías et al, 2011).…”
Section: Role Of Aba In Plant Growth and Developmentmentioning
confidence: 99%
“…cDNA samples were Cy5-labelled and co-hybridized with a Cy3-labelled cDNA reference pool from a mixture containing equal amounts of RNA from all experimental samples assayed. The use of this reference sample has been widely used in Citrus transcriptomic research since it represents a powerful tool for reducing the number of hybridizations to make all the possible pairwise comparisons between samples (Agustí et al, 2008).…”
Section: Rna Isolation Cdna Labelling and Microarray Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Con estas colecciones de ESTs se ha elaborado una micromatriz que contiene 21081 unigenes (Martinez-Godoy et al, 2008) y que está siendo utilizada por distintos grupos de investigación para definir patrones de expresión génica en distintos tejidos, estadios del desarrollo del fruto (floración, fructificación, maduración) (Cercós et al, 2006;Alós et al, 2008) como respuesta a diversos tratamientos de estrés abiótico (salinidad, sequía, deficiencia en hierro, etc.) (Agustí et al, 2008;Huerta et al, 2008) o biótico (virus, hongos, etc. ) (Gandía et al, 2007) y para distinguir variedades .…”
Section: Mejora Genética De Los Cítricosunclassified